2021
DOI: 10.1155/2021/6682456
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Grained Task Access Control System for Mobile Crowdsensing

Abstract: Mobile crowdsensing enables people to collect and process a massive amount of information by using social resources without any cost on sensor deployment or model training. Many schemes focusing on the problems of task assignment and privacy preservation have been proposed so far. However, the privacy-preserving of requesters and task access control, which are vital to mobile crowdsensing, is barely considered in the literature. To address the aforementioned issues, a fine-grained task access control system fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Focus on the efficiency improvement, Tang et al [33] indicated to alleviate the computational overheads of task encryption and decryption phase with online/offline encryption [34] and outsourced decryption [35] technology and designed to recommend the optimal task for task performers with the claimed "win-win" strategy. More recently, Wang et al [10] presented a fine-grained access control protocol for the mobile crowdsensing platform, which enables the lightweight keyword generation and search and specifies the crowdsensing platform to predecrypt the ciphertext to reduce the computational overheads of the task performer side. However, their proposal is insecure unless they assumed the crowdsensing platform to be fully trusted, since they direct deliver the performer's user secret key to the crowdsensing platform.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Focus on the efficiency improvement, Tang et al [33] indicated to alleviate the computational overheads of task encryption and decryption phase with online/offline encryption [34] and outsourced decryption [35] technology and designed to recommend the optimal task for task performers with the claimed "win-win" strategy. More recently, Wang et al [10] presented a fine-grained access control protocol for the mobile crowdsensing platform, which enables the lightweight keyword generation and search and specifies the crowdsensing platform to predecrypt the ciphertext to reduce the computational overheads of the task performer side. However, their proposal is insecure unless they assumed the crowdsensing platform to be fully trusted, since they direct deliver the performer's user secret key to the crowdsensing platform.…”
Section: Related Workmentioning
confidence: 99%
“…As a flexible crowdsensing strategy emphasizes open participation, participatory mobile crowdsensing enables the urban administrator to publish some "tasks" in the crowdsensing platform, and then, any resident owns a fair opportunity to bid for these tasks. In a more professional view, as illustrated in Figure 1 [10], the urban administrator acts as the requester, designs, and releases tasks to the crowdsensing platform.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations